2002
DOI: 10.1046/j.1570-7458.2002.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixing barley cultivars affects aphid host plant acceptance in field experiments

Abstract: Four barley varieties with no significant difference in aphid acceptance were sown in pure stands and in pairwise combinations with varieties side by side in separate rows. Settling tests were done in situ in the field plots with apterae of Rhopalosiphum padi (L.) (Homoptera:Aphididae) and showed that aphid acceptance was changed in some combinations of cultivars. In a laboratory test, in which plants of one cultivar were exposed to air from the other cultivars, aphid acceptance was significantly reduced in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 24 publications
6
86
1
Order By: Relevance
“…Plants were placed inside modified Perspex cages (each 10 9 10 9 40 cm), with an opening (7 cm diameter) in the front side (Ninkovic et al 2002). Pots with test plants were placed in Petri dish lids to prevent any contact with root exudates from neighbouring plants.…”
Section: Touching Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants were placed inside modified Perspex cages (each 10 9 10 9 40 cm), with an opening (7 cm diameter) in the front side (Ninkovic et al 2002). Pots with test plants were placed in Petri dish lids to prevent any contact with root exudates from neighbouring plants.…”
Section: Touching Treatmentmentioning
confidence: 99%
“…An aphid no-choice settling test (Ninkovic et al 2002) was used to investigate aphid behavioural response to touched and untouched plants. Both maize and bean plants were tested 24 h after the last touching treatment ended.…”
Section: Aphid Settling Testmentioning
confidence: 99%
“…These DH lines were selected for further studies because they caused greater reductions in aphid growth compared to their DH siblings. In addition, cultivars Alva and Kara were included in the studies because they have previously shown allelobiosis effects (Ninkovic et al 2002).…”
Section: Plant Materialsmentioning
confidence: 99%
“…In parallel studies, it has been shown that volatiles from undamaged barley plants can, in certain cultivar combinations, reduce R. padi acceptance of the volatile-exposed plants (Pettersson et al 1999;Ninkovic et al 2002). It has also been shown that exposure to volatiles from Cirsium spp.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation